2011
DOI: 10.1002/nau.21044
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence: An under‐recognized risk factor for falls among elderly dementia patients

Abstract: Urinary incontinence is a previously unidentified risk factor for falls among elderly dementia patients. An interventional study with the focus of urinary incontinence could improve the effectiveness of fall prevention among these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 36 publications
2
25
1
4
Order By: Relevance
“…Overactive bladder syndrome is the most common cause of urinary incontinence in older adults . Our study aimed at analyzing the association between this pervasive condition and the risk of falls among older adult Medicare fee‐for‐service enrollees.…”
Section: Discussionmentioning
confidence: 99%
“…Overactive bladder syndrome is the most common cause of urinary incontinence in older adults . Our study aimed at analyzing the association between this pervasive condition and the risk of falls among older adult Medicare fee‐for‐service enrollees.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary incontinence is a known risk factor for falls among elderly persons with dementia. (24) Urinary incontinence is about four times more common among elderly persons with dementia than those without. Among elderly persons with dementia, the prevalence of urinary incontinence was found to range between 22% (community-dwelling) and 84% (residing in a nursing home).…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort study, the use of 4 or more medications was associated with increased risk of falling and the risk of recurrent falls [37]. A study in elderly patients with dementia reported that those patients who reported a fall had an increased prevalence of polypharmacy [38]. In a study of institutionalized older adults the risk of experiencing a fall within the previous 30 days was by 7% for each additional medication [39].…”
Section: 0 Consequences Of Polypharmacymentioning
confidence: 99%